Collective Bargaining for Women: How Unions Can Create Female-Friendly Jobs - Viola Corradini; Lorenzo Lagos; Garima Sharma (The Quarterly Journal of Economics, 2025)
ABSTRACT We study the role of unions in improving workplaces for women. Starting in 2015, Brazil’s largest trade union federation made women central to its agenda. Using a difference-in-differences design that leverages variation in union affiliation to this federation, we find that “bargaining for women” increased female-friendly amenities in collective bargaining agreements and in practice. These changes led women to queue for jobs at treated establishments and separate from them less—both revealed-preference measures of firm value. We find no evidence that gains came at the expense of wages, employment, or firm profits. Better amenities instead reduced turnover and absenteeism, suggesting greater worker satisfaction and effort. Larger improvements occurred where women initially composed a lower share of workers or union leaders. Our findings show that shifting union priorities toward women improved workplaces without meaningful trade-offs and benefited both workers and employers. They illustrate the potential for unions to improve workplace quality by focusing on the needs of less represented workers.